Approaches to interventional fluoroscopic dose curves - Wunderle, Kevin A. (J Appl Clin Med Phys, 2016)
Modern fluoroscopes used for image‐based guidance in interventional procedures are complex X‐ray machines, with advanced image acquisition and processing systems capable of automatically controlling numerous parameters based on defined protocol settings. This study evaluated and compared approaches to technique factor modulation and air kerma rates in response to simulated patient thickness variations for four state‐of‐the‐art and one previous‐generation interventional fluoroscopes. A polymethyl methacrylate (PMMA) phantom was used as a tissue surrogate for the purposes of determining fluoroscopic reference plane air kerma rates, kVp, mA, and variable copper filter thickness over a wide range of simulated tissue thicknesses. Data were acquired for each fluoroscopic and acquisition dose curve within each vendor's default abdomen or body imaging protocol. The data obtained indicated vendor‐ and model‐specific variations in the approach to technique factor modulation and reference plane air kerma rates across a range of tissue thicknesses. However, in the imaging protocol evaluated, all of the state‐of‐the‐art systems had relatively low air kerma rates in the fluoroscopic low‐dose imaging mode as compared to the previous‐generation unit. Each of the newest‐generation systems also employ Cu filtration within the selected protocol in the acquisition mode of imaging; this is a substantial benefit, reducing the skin entrance dose to the patient in the highest dose‐rate mode of fluoroscope operation. Some vendors have also enhanced the radiation output capabilities of their fluoroscopes which, under specific conditions, may be beneficial; however, these increased output capabilities also have the potential to lead to unnecessarily high dose rates. Understanding how fluoroscopic technique factors are modulated provides insight into the vendor‐specific image acquisition approach and may provide opportunities to optimize the imaging protocols for clinical practice. PACS number: 87.59.C‐